Distinct morphological and behavioural alterations in enu-induced heterozygous trpc7k810stop mutant mice - Rathkolb, Birgit; Howaldt, Maike; Krebs, Stefan; Prückl, Petra; Sauer, Susanne; de Angelis, Martin Hrabě; Aigner, Bernhard (Genes, 2021)
Trpc7 (transient receptor potential cation channel, subfamily C, member 7; 862 amino acids) knockout mice are described showing no clear phenotypic alterations, therefore, the functional relevance of the gene remains unclear. A complementary approach for the functional analysis of a given gene is the examination of individuals harbouring a mutant allele of the gene. In the phenotype-driven Munich ENU mouse mutagenesis project, a high number of phenotypic parameters was used for establishing novel mouse models on the genetic background of C3H inbred mice. The phenotypically dominant mutant line SMA002 was established and further examined. Analysis of the causative mutation as well as the phenotypic characterization of the mutant line were carried out. The causative mutation was detected in the gene Trpc7 which leads to the production of a truncated protein due to the novel stop codon at amino acid position 810 thereby affecting the highly conserved cytoplasmic C terminus of the protein. Trpc7 heterozygous mutant mice of both sexes were viable and fertile, but showed distinct morphological and behavioural alterations which is in contrast to the published phenotype of Trpc7 knockout mice. Thus, the Trpc7K810Stop mutation leads to a dominant negative effect of the mutant protein.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Animal model; Growth; Seizure; Tissue irritation; TRPC7